2005
DOI: 10.1002/mds.20559
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal intranuclear inclusion disease: Report on a case originally diagnosed as dopa‐responsive dystonia with Lewy bodies

Abstract: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder with a heterogeneous clinical picture characterized by the presence of eosinophilic intranuclear inclusions in neuronal and glial cells. We describe a case, reported 12 years ago as dopa-responsive dystonia (DRD) with Lewy body pathology. Pathological re-examination has led to a revised diagnosis of neuronal intranuclear inclusion disease. This rare condition, which may be diagnosed in life with a full thickness rectal biopsy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…Furthermore, we reported that, in this study, tremor, rigidity and general convulsions were rarely observed in adult-onset NIID (Table 2), and these manifestations were frequently reported in infantile and juvenile NIID cases (Sung et al , 1980; Haltia et al , 1984; Funata et al , 1990; Sloane et al , 1994; O'Sullivan et al , 2000; Paviour et al , 2005). Clinical features of infant, juvenile and adult NIID are different, but some clinical manifestations are common to them.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, we reported that, in this study, tremor, rigidity and general convulsions were rarely observed in adult-onset NIID (Table 2), and these manifestations were frequently reported in infantile and juvenile NIID cases (Sung et al , 1980; Haltia et al , 1984; Funata et al , 1990; Sloane et al , 1994; O'Sullivan et al , 2000; Paviour et al , 2005). Clinical features of infant, juvenile and adult NIID are different, but some clinical manifestations are common to them.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, neuronal loss is often present, though not in the brain regions in which inclusions are present. In marked contrast to published cases, the ubiquitinated inclusions in our case were not detected in LH&E or H&E -stained sections [2224]. Hence, this patient had a pattern of pathological change that has apparently not been reported previously in the literature.…”
Section: Discussioncontrasting
confidence: 97%
“…Neuronal intranuclear inclusion disease is a rare neurodegenerative disorder with a heterogeneous clinical picture that can include parkinsonism, cerebellar signs, pyramidal tract signs, and dementia accompanied by the diffuse presence of ubiquitin positive inclusions in the brain [2224]. In addition, neuronal loss is often present, though not in the brain regions in which inclusions are present.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological diagnosis can be made ante‐mortem on full‐thickness rectal biopsy with intranuclear inclusions and neuronal death in the myenteric plexus. Similar pathological involvement of the substantia nigra has been demonstrated at autopsy in other cases of NIID causing L ‐dopa‐responsive JP 7, 14…”
Section: Discussantsupporting
confidence: 74%
“…During the diagnostic efforts, the clinicians involved in the care of this patient found support in their migration from a diagnosis of DRD to NIID from a similar juvenile parkinsonian case reported as “DRD with Lewy bodies.” As in this case, that report described marked L ‐dopa responsiveness, oculogyric crises, and decreased HVA in CSF 16. A shrewd group of neurologists, keenly aware of the rarity of Lewy bodies in juvenile Parkinsonism, re‐examined the pathology of the case over a decade later and determined that the eosinophilic and ubiquitinated inclusions were actually intranuclear, indeed revising the diagnosis to NIID 14. This diagnostic revision was spearheaded by one of the discussants (DCP), who is also the first author of an excellent review on juvenile Parkinsonism the readers are encouraged to consult 9.…”
Section: Learning Pointsmentioning
confidence: 65%